2021
DOI: 10.1007/s00125-021-05538-9
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of heterogeneous nuclear ribonucleoprotein F in renal tubules downregulates SGLT2 expression and attenuates hyperfiltration and kidney injury in a mouse model of diabetes

Abstract: Aims/hypothesis We previously reported that renal tubule-specific deletion of heterogeneous nuclear ribonucleoprotein F (Hnrnpf) results in upregulation of renal angiotensinogen (Agt) and downregulation of sodium-glucose co-transporter 2 (Sglt2) in Hnrnpf RT knockout (KO) mice. Non-diabetic Hnrnpf RT KO mice develop hypertension, renal interstitial fibrosis and glycosuria with no renoprotective effect from downregulated Sglt2 expression. Here, we investigated the effect of renal tubular Hnrnpf deletion on hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“… 46 In addition, hnRNPF has been reported to be implicated in the kidney injury in diabetic mice by regulating the transcription of a series of genes, including Sirt1 and Ace2 . 30 , 31 , 32 , 33 , 34 Consistently, our study uncovered that in β cells, hnRNPF could activate the transcription of Sirt1 , a NAD + -dependent histone deacetylase that regulates insulin secretion and promotes β-cell survival by deacetylating histones and a dozen nonhistone proteins. 47 , 48 Furthermore, we found that knockdown of hnRNPF induced β-cell dysfunction by reducing Sirt1 expression levels, suggesting that hnRNPF may play an important role in maintaining β-cell function.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“… 46 In addition, hnRNPF has been reported to be implicated in the kidney injury in diabetic mice by regulating the transcription of a series of genes, including Sirt1 and Ace2 . 30 , 31 , 32 , 33 , 34 Consistently, our study uncovered that in β cells, hnRNPF could activate the transcription of Sirt1 , a NAD + -dependent histone deacetylase that regulates insulin secretion and promotes β-cell survival by deacetylating histones and a dozen nonhistone proteins. 47 , 48 Furthermore, we found that knockdown of hnRNPF induced β-cell dysfunction by reducing Sirt1 expression levels, suggesting that hnRNPF may play an important role in maintaining β-cell function.…”
Section: Discussionsupporting
confidence: 80%
“… 29 Studies have shown that hnRNPF participated in kidney injury in diabetic mice. 30 , 31 To further elucidate the functional roles of hnRNPF in β cells, hnRNPF was knocked down using siRNAs ( Figure 3 A). Silencing hnRNPF significantly reduced cell viability and proliferation, inhibited insulin secretion, and increased cell apoptosis in MIN6 cells and islets, suggesting an important role of hnRNPF in regulating β-cell function ( Figures 3 B–3F and S3 A–S3C).…”
Section: Resultsmentioning
confidence: 99%
“…This may allow myofibroblasts in the mesenchyme to reverse to some extent to erythropoietin-producing fibroblasts, enhancing the hematopoiesis and elevating hematocrit ( 49 ). Some other studies suggest that SGLT2i can prevent damage to renal mesenchymal cells by reducing the activity of the SGLT2 pathway on proximal tubular cells, and this will maintain an adequate erythropoietin level, and subsequently increase hemoglobin and hematocrit levels ( 50 , 51 ). It has also been found in other studies that the increase of hematocrit may be closely related to the correction of sympathetic hyperfunction, leading to the reduction of cardiovascular mortality and the risk of hospitalization due to heart failure ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The most effective treatment to improve the survival rate of ESRD patients is kidney transplantation; however, insufficient kidney donors and prohibitively high cost make it impossible for many ESRD patients to receive kidney transplantation. 5 New agents such as SGLT2 inhibitors and finerenone have shown the capability to reduce the progression of chronic kidney disease (CKD) by inhibiting the angiotensin converting enzyme or blocking angiotensin receptors, 6,7 and these two drugs stand a high chance of curbing the progression of renal fibrosisa common pathological finding in CKD. However, no drugs have yet been approved by the FDA specifically for treating renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%